The Relationship Of Young Women’s Knowledge Of Human Papilloma Virus (HPV) Vaccination With Attitudes In Cervical Cancer Prevention At MTS Nurul Ikhlas Tabing Sub-District Koto Kampar Hulu - Feni Amelia; Yulia Febrianita (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Background : Cervical cancer is one type of cancer whose growth is very rapid and alarming. The problem of cervical cancer in Indonesia can be prevented with the HPV vaccination program. HPV vaccination can be recommended to be given to women aged 9-12 years. Objective : The purpose of this study was to identify the relationship between adolescent girls' knowledge about Human Papilloma Virus (HPV) vaccination with attitudes in cervical cancer prevention at MTs Nurul Ikhlas Tabing, Koto Kampar Hulu District. Methodology : This type of research is quantitative research with a correlative analytical research design with a cross sectional approach. This study used a total sampling technique with a sample of 79 respondents. The instrument for data collection is in the form of a questionnaire by providing 30 questions. Data were analyzed using univariate and bivariate analysis. The results of the statistical test show that the p value = 0.01 > α 0.05. Results : The results of the study found that the majority of adolescent girls had good knowledge about Human Papilloma Virus (HPV) vaccination 51 people (64.6%) and adolescent girls had a positive attitude in preventing cervical cancer 45 people (57.0%). It can be concluded that there is a significant relationship between adolescent girls' knowledge about Human Papilloma Virus (HPV) vaccination with attitudes in cervical cancer prevention at MTs Nurul Ikhlas Tabing, Koto Kampar Hulu District. Suggestion: For health workers to be more active in providing information on how to prevent cervical cancer by immunizing the HPV vaccine in the form of counseling, leaflets and takeouts, so that adolescent girls can pay attention to reproductive health which will have an impact on reducing morbidity and death rates due to cervical cancer.